2021
DOI: 10.1093/gerona/glab094
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Physical Activity, Blood-Based Biomarkers of Neurodegeneration, and Cognition in Healthy Older Adults: The MAPT Study

Abstract: Physical activity (PA) demonstrated benefits on brain health but its relationship with blood biomarkers of neurodegeneration remains poorly investigated. We explored the cross-sectional associations of physical activity with blood concentrations of neurofilament light chain (NFL) and beta amyloid (Aβ)42/40. We further examined whether the interaction between PA and these biomarkers was longitudinally related with cognition. Four-hundred and sixty-five non-demented older adults engaged in an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
2
16
1
Order By: Relevance
“… 3 Examining the associations between AD biomarkers and health behaviors such as physical activity is a new area of research. 25 We found only 1 study, the Multidomain Alzheimer Preventive Trial (MAPT), 26 that evaluated associations between NfL concentrations in blood and physical activity over 4 years. In that study, high NfL concentrations were associated with reductions in the benefits of physical activity on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Examining the associations between AD biomarkers and health behaviors such as physical activity is a new area of research. 25 We found only 1 study, the Multidomain Alzheimer Preventive Trial (MAPT), 26 that evaluated associations between NfL concentrations in blood and physical activity over 4 years. In that study, high NfL concentrations were associated with reductions in the benefits of physical activity on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, high NfL concentrations were associated with reductions in the benefits of physical activity on cognitive function. Investigators have called for the need to validate results and to examine the associations between physical activity and NfL concentrations in a sample that has not received intervention . The present study leveraged the longitudinal cohort design and population-based sample of CHAP to address this need.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, higher CSF NfL levels have been associated with slower gait speed, 20 but similar associations did not replicate by using plasma NfL levels in another secondary analysis of the MAPT Study 6 . While Raffin et al demonstrated a cross‐sectional association between physical inactivity and higher NfL levels in blood among MAPT participants, 21 Jensen et al found no effect of exercise training on the change of CSF NfL concentrations in AD patients 22 . Noteworthy, our sensitivity analysis found that individuals with high plasma NfL levels were more likely to experience exhaustion at baseline; a similar association was observed for plasma PGRN using categorical measures.…”
Section: Discussionmentioning
confidence: 99%
“…To take into account potential confounding factors, the following variables were considered: age, sex, body mass index (BMI = weight (kg)/height (m) 2 ), diagnosis of arterial hypertension or diabetes, physical activity (minutes per week) and allocation to MAPT intervention groups. History of smoking and alcohol intake was not included in the analysis because data were available for less than half of the participants 22 .…”
Section: Methodsmentioning
confidence: 99%